CHARACTERIZATION OF THE RELIABILITY OF RADIO COMMUNICATIONS WITH AIR TRAFFIC SERVICES - E. I. Grigorieva; M. U. Zamaldinov (Научный вестник МГТУ ГА)
Convert formulas to calculate the availability of the radio channel in a compact form, and the graph of depend-ence of the excess signal power at the receiver input over its actual sensitivity of the level of interference, while ensuring the required value of the availability of the radio channel.